An Assessment of the Asphalt Fatigue Equation for Bitumen Stabilised Materials - Dadras, Ethan (Curtin University, 2016)
The aim of this research is to characterise the laboratory fatigue performance of a typical foamed bitumen mix used in Western Australia. It has also investigated the applicability of Austroads fatigue equation for the design of in-situ foamed bitumen stabilised materials. A new four-point bending device was utilised as a scaled up version which allows testing of much larger beams by removing the constraint that the maximum width and thickness are dominated by maximum aggregate size.